Popular contemporary window display composition and its influences on youths in Malaysia / Nor Aishah Zaha Zainal Abidin and Azlaini Haji Abdul Aziz - Zainal Abidin, Nor Aishah Zaha (Faculty of Architecture, Planning and Surveying, 2011)
Consumers’ expectations from retailers increase with the expanding market demand, where diversification in business strategies to satisfy consumer’s expectations has become a managerial concern. Window display is one of the marketing methods that sells in silence, helps better decision making and improves the store’s image. This paper will critically analyse the application of window display at shopping malls in Kuala Lumpur. The investigation will help establish a better understanding of how the window display works in conveying product meaning, value and quality correctly towards youth consumer, while assisting in improving meaning transfer that leads to strategic merchandising messages and sales.